POMD07 Quantitative assessment of biological and clinical manifestations of Huntington's disease before and after diagnosis—the TRACK-HD study. Issue 11 (22nd October 2010) - Lahiri, N; Tabrizi, S J; Kennard, C; Durr, A; Leavitt, B R; Fox, N; Roos, R A
Abstract : Background: Huntington's disease (HD) is a fully penetrant dominantly inherited neurodegenerative disease. The aim of this study was to identify sensitive and reliable biomarkers in clinically premanifest HD gene carriers and early HD patients. Methods: TRACK-HD is a multinational longitudinal observational study that uses an extensive battery of assessments including 3-T MR imaging, clinical, cognitive, quantitative motor, oculomotor and neuropsychiatric measures. Blinded analysis was performed on the baseline cross-sectional data which included 366 subjects (123 controls, 123 early HD, 120 premanifest subjects). Results: Cross-sectional analysis identified significant changes in whole-brain volume, regional grey and white matter, impairment in a range of voluntary motor physiology and oculomotor tasks, cognitive and neuropsychiatric dysfunction in premanifest HD gene carriers through to early clinical stage II disease. Conclusions: Our results provide evidence for quantifiable biological and clinical alterations in HD expansion carriers compared to age-matched controls. Many parameters differ from age-matched controls in a graded fashion showing changes of increasing magnitude covering two decades of disease development from pre-HD up to ∼16 years from predicted onset through to HD stage II. These findings help to define novel quantifiable endpoints and methods for rapid and reliable multisite data acquisition that form the essential foundation to design therapeutic trials.